Designed to Fit: The Development and Validation of the STRONG-R Recidivism Risk Assessment. (February 2016) - Hamilton, Zachary; Kigerl, Alex; Campagna, Michael; Barnoski, Robert; Lee, Stephen; van Wormer, Jacqueline; Block, Lauren
Recidivism risk assessment tools have been utilized for decades. Although their implementation and use have the potential to touch nearly every aspect of the correctional system, the creation and examination of optimal development methods have been restricted to a small group of instrument developers. Furthermore, the methodological variation among common instruments used nationally is substantial. The current study examines this variation by reviewing methodologies used to develop several existing assessments and then tests a variety of design variations in an attempt to isolate and select those which provide improved content and predictive performance using a large sample ( N = 44, 010) of reentering offenders in Washington State. Study efforts were completed in an attempt to isolate and identify potential incremental performance achievements. Findings identify a methodology for improved prediction model performance and, in turn, describe the development and introduction of the Washington State Department of Correction's recidivism prediction instrument—the Static Risk Offender Need Guide for Recidivism (STRONG-R).